Study of the Digitalization for the Labor Market - Zata Hasyyati; Jodi Hendrawan; Fauzul Azman (Universitas 17 Agustus 1945 Semarang, 2023)
The discovery of various efficient technologies has become a benchmark in development in all sectors. Artificial Intelligence (AI) and the Internet of Things (IoT) are growing rapidly. This study aims to determine the analysis of the technological adaptability of countries in the world and its comparison to readiness in Indonesia. This is because the ability to adapt technology has a close relationship to the economy in a country, both in terms of economic contribution and the labor market sector. This research uses data with parameters such as Gross Market Value (GMV), Global Connectivity Index (GCI), and GDP. As well as data on industry development in Indonesia. This research was conducted with a descriptive analysis method that uses content analysis steps to interpret the results of existing statistical exposure. The results of the research analysis show that a very significant government policy today is an investment in technology and communication infrastructure. Then to boost the economy, financing is the most needed factor today. Readiness to meet the demographic bonus can be done by developing the digital skills of the workforce in all sectors. Therefore, infrastructure, financing, and scientific integration of technology are the most crucial policies today.